2021
DOI: 10.1007/s12652-021-03464-7
|View full text |Cite
|
Sign up to set email alerts
|

Detection and classification of lung diseases for pneumonia and Covid-19 using machine and deep learning techniques

Abstract: Since the arrival of the novel Covid-19, several types of researches have been initiated for its accurate prediction across the world. The earlier lung disease pneumonia is closely related to Covid-19, as several patients died due to high chest congestion (pneumonic condition). It is challenging to differentiate Covid-19 and pneumonia lung diseases for medical experts. The chest X-ray imaging is the most reliable method for lung disease prediction. In this paper, we propose a novel framework for the lung disea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
59
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(59 citation statements)
references
References 51 publications
0
59
0
Order By: Relevance
“…The three best models were selected based on their performance for the heterogeneous stacked ensemble. Goyal and Singh [41] used machine learning and deep learning technique for the early detection of COVID-19. They first used a median filter followed by the histogram equalization to enhance the image quality.…”
Section: Deep Learning Methodsmentioning
confidence: 99%
“…The three best models were selected based on their performance for the heterogeneous stacked ensemble. Goyal and Singh [41] used machine learning and deep learning technique for the early detection of COVID-19. They first used a median filter followed by the histogram equalization to enhance the image quality.…”
Section: Deep Learning Methodsmentioning
confidence: 99%
“…These methods were able to perform well with the use of the deep features. For example, Goyal and Singh (2021) designed fusion and normalization features based recurrent neural network (RNN)-long short-term memory (LSTM) (abbreviated as F-RNN-LSTM) that relied on only handcrafted features comprised of Gray-level Co-occurrence Matrix (GLCM), histogram of oriented gradients (HOG), intensity and geometric features. However, this model was empowered with a deep learner known as RNN-LSTM model.…”
Section: Related Workmentioning
confidence: 99%
“…In this context, it is to be noted that Rahman, et al (2021) studied, in detail, the effect of various image enhancement techniques on COVID-19 detection using some standard CNN models. Also, Goyal and Singh (2021) used histogram equalization to enhance the quality before applying an adaptive image segmentation method to extract the region of interest, which was then used for classification purposes.…”
Section: Related Workmentioning
confidence: 99%
“…During the last two decades, Deep Learning (DL) architectures (Devunooru et al. 2021 ; Goyal and Singh 2021 ) have demonstrated their ability to deal with more voluminous and complex data. Moreover, it has gradually become the most widely used computational approach in the field of ML, achieving outstanding results on several cognitive tasks, matching or even beating those reached by human performance.…”
Section: Introductionmentioning
confidence: 99%
“…ML research achieved outstanding results on several complex cognitive tasks, including Computer Vision Alsarhan et al (2021), Medical diagnoses Chaabene et al (2021); Sree et al (2021), Signal Processing Jaini et al (2021), etc. During the last two decades, Deep Learning (DL) architectures Devunooru et al (2021); Goyal and Singh (2021) have demonstrated their ability to deal with more voluminous and complex data. Moreover, it has gradually become the most widely used computational approach in the field of ML, achieving outstanding results on several cognitive tasks, matching or even beating those reached by human performance.…”
Section: Introductionmentioning
confidence: 99%